An environmentally friendly reflectometric method for ranitidine determination in pharmaceuticals and human urine - Lima, Liliane Spazzapam [UNESP]; Weinert, Patricia Los [UNESP]; Lemos, Sahra Cavalcante [UNESP]; Sequinel, Rodrigo [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
This paper describes an environmentally friendly method for quantitative determination of ranitidine using diffuse reflectance spectroscopy. This method is based on the reflectance measurements of the colored product produced from the spot test reaction between ranitidine and p-dimethylaminocinnamaldehyde (p-DAC), in acid medium, using filter paper as solid support. Experimental design methodologies were used to optimize the optimal conditions. All reflectance measurements were carried out at 590 nm and the linear range was from 1.42 x 10(-3) to 3.42 x 10(-2) mol L(-1), with a correlation coefficient of 0.997. The limit of detection was estimated to be 1.09 x 10(-3) mol L(-1) (R.S.D. = 1.9%). The proposed method was successfully applied to the determination of ranitidine in commercial brands of pharmaceuticals and no interferences were observed from the common excipients in formulations. The results obtained by the proposed method were favorably compared with those obtained by an official procedure at 95% confidence level. Additionally, the method was also applied to the determination of ranitidine in human urine showing excellent recoveries (99.6-100.3%). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ranitidine; Diffuse reflectance spectroscopy; Spot test; Pharmaceuticals; Human urine